Reactive crisis strategies application of the corporate sector in Croatia. Issue 2 (2nd May 2017) - Jugo, Damir
Abstract : Purpose: The purpose of this paper is to examine the practices of strategic crisis communication of most successful Croatian companies and the perception of these practices from the perspective of media. A framework of reactive strategies is applied to determine how Croatian companies from five major industries would communicate during crisis situations and how their communication is interpreted within the media as a group that conveys and presents their behavior and communication to the broader public. Design/methodology/approach: A quantitative survey among 60 individuals in charge of communications in Croatian companies was conducted to identify which strategies they are likely to use when in crisis situations. In-depth interviews with 20 journalists regularly reporting on these companies were undertaken to determine their perception and experiences regarding how these companies would communicate during crisis situations. Findings: Croatian companies are likely to communicate un-strategically, passively and without any risk. Journalists see the communication of the companies even more passive and reactive which seriously influences the manner they report about these companies during crisis situations. Research limitations/implications: Although 60 companies and 20 journalists both represent a significantly representative sample in Croatian terms, the study provides an insight into only Croatian corporate environment. Conducting the research in different surroundings and other countries could provide additional insight. Nevertheless, the analyzed variables that influenced the selection of strategies provide notable insight for drawing conclusions on this subject. Originality/value: Besides showing how analyzed companies are likely to communicate during crises, this paper provides an insight into the media's perception of this communication. The research has shown that the media sees their communication as more passive and reactive than it actually is, which implicates a serious need of shift in communication patterns if these companies want to strive to gain mutual understanding and remotely positive attitude from the media during crisis situations.